2017
DOI: 10.1016/j.resuscitation.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

2017 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations Summary

Abstract: The International Liaison Committee on Resuscitation has initiated a near-continuous review of cardiopulmonary resuscitation science that replaces the previous 5-year cyclic batch-and-queue approach process. This is the first of an annual series of International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations summary articles that will include the cardiopulmonary resuscitation science reviewed by the International Liaison Committee on Resuscit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 55 publications
1
47
0
16
Order By: Relevance
“…1 It aligns with the International Liaison Committee on Resuscitation's continuous evidence review process, and updates are published when the International Liaison Committee on Resuscitation completes a literature review based on new science. A description of the evidence review process is available in the "2017 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations Summary," 1 and a glossary of terms is available in that document. The International Liaison Committee on Resuscitation's Grading of Recommendations Assessment, Development, and Evaluation assessments were converted to the American College of Cardiology/American Heart Association Classes of Recommendations and Levels of Evidence (Table).…”
mentioning
confidence: 99%
“…1 It aligns with the International Liaison Committee on Resuscitation's continuous evidence review process, and updates are published when the International Liaison Committee on Resuscitation completes a literature review based on new science. A description of the evidence review process is available in the "2017 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations Summary," 1 and a glossary of terms is available in that document. The International Liaison Committee on Resuscitation's Grading of Recommendations Assessment, Development, and Evaluation assessments were converted to the American College of Cardiology/American Heart Association Classes of Recommendations and Levels of Evidence (Table).…”
mentioning
confidence: 99%
“…There are many other evidence appraisal methods, each with advantages and disadvantages ( Atkins et al 2004 ), some of which are continuously re-developed to overcome identified shortcomings. The Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) approach has been widely implemented ( Guyatt et al 2008 ), including into the International Liaison Committee on Resuscitation (ILCOR) evidence review process ( Olasveengen et al 2017 ). GRADE evaluates evidence for specific questions by outcome, which differs from PEP, which evaluates all related evidence per specific intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Compression only CPR maybe associated with poorer outcomes than conventional CPR in human clinical patients ( 22 24 ). Despite this, it is currently recommended for out of hospital CPR in humans for untrained rescuers, as it has been found to be associated with a higher rate of bystander CPR provision ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%